Attitudinal model predictor of academic performance of pre-service teachers - Navalta, Czar Justine D. (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the study is to create a model of academic performance in Professional Education subjects as influenced by the students’ learning attitude-related variables. By utilizing a descriptive-correlational research design, this study determined the significant relationship between attitude and academic performance of the students, which were utilized in creating a mathematical model. With 154 respondents, it was found that the respondents had a positive attitude towards learning Professional Education Subjects and performed very satisfactorily, and their degree courses had an influence on their level of commitment and knowledge of the subject matter towards learning Professional Education Subjects. However, the model’s predictability is relatively low. It can be concluded that while students are committed, knowledgeable, learn independently, and have a keen sense of management in learning Professional Education Subjects, the learning attitude variables have a low predictive power on their academic performance. The implications of the study recommend exploring other factors that could affect their academic performance to achieve better predictability models. Teachers must encourage students to perform better in their Professional Education Subjects by reinforcing a positive attitude towards learning.